Working with fractions - Adler, David A.; Miller, Edward, 1964- (New York : Holiday House, 2007)
Shows how to calculate and use simple fractions, presenting examples involving everyday activities such as counting money, playing games, and splitting up a pizza.
Booklist.
Horn Book.
Kirkus Review.
5.1
3-6
Keywords: Fractions -- Juvenile literature; Fractions; Fractions